Oil palm production and cooperatives in the Philippines - Katsumi Nozawa (University of the Philippines, School of Economics (UPSE), 2011)
The promotion of oil palm production as an agribusiness development policy is a major issue in response to the increasing demand of palm oil in the Philippines. This paper focused on oil palm production cooperatives composed of agrarian reform beneficiaries (ARBs) as members who were granted the Certificate of Land Ownership Award (CLOA). The paper scrutinized the difference of farm incomes with the land titles between the Individual CLOA and the Collective CLOA under the Agribusiness Venture Arrangement (AVA) mode through the field survey of the cooperatives in the provinces in Mindanao. In conclusion, the proposal was made with the emphasis on the necessity to provide production technology and management skill to the cooperatives and its ARBs members with the special emphasis given to those granted the Collective CLOA through the various kinds of agricultural assistance.
Keywords: 330; oil palm production; agribusiness; cooperative; agrarian reform beneficiaries; Agribusiness Venture Arrangement; contract growing; lease arrangement; Certificate of Land Ownership Award; Palmöl; Agrarproduktion; Agrargenossenschaft; Agrarreform; Agrareinkommen; Philippinen